2006
DOI: 10.4103/0019-509x.25890
|View full text |Cite
|
Sign up to set email alerts
|

Samarium-153 ethylenediamine tetramethylene phosphonate therapy for bone pain palliation in skeletal metastases

Abstract: BACKGROUND: Systemic therapy with radionuclides may be used for the treatment of patients with painful skeletal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 15 publications
4
19
0
1
Order By: Relevance
“…After injection of 153Sm-EDTMP, response was recognized in 90.3% prostate cancer and 97.9% of breast cancer patients, a total of 7/110 prostate and breast cancer patients did not respond to therapy. As compared with other studies showed 40 to 85.5% response rates in cancer breast and 70 to 80% response rate in cancer prostate [16][17][18], we reported insignificant difference in therapeutic response rate between prostate and breast cancer (90.5% and 97.8% respectively), this finding also recorded by Tripathi et al as well as Baczyk et al who did not show any significant difference in response rate among prostate and breast cancer patients (80.6% and 80.4%) respectively [11,19].…”
Section: Discussionsupporting
confidence: 77%
“…After injection of 153Sm-EDTMP, response was recognized in 90.3% prostate cancer and 97.9% of breast cancer patients, a total of 7/110 prostate and breast cancer patients did not respond to therapy. As compared with other studies showed 40 to 85.5% response rates in cancer breast and 70 to 80% response rate in cancer prostate [16][17][18], we reported insignificant difference in therapeutic response rate between prostate and breast cancer (90.5% and 97.8% respectively), this finding also recorded by Tripathi et al as well as Baczyk et al who did not show any significant difference in response rate among prostate and breast cancer patients (80.6% and 80.4%) respectively [11,19].…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, neuropathic pain is first treated as nociceptive pain, but if there is no relief the treatment can be supplemented by tricyclic antidepressants and antiepileptic medications. Hormonal therapy and chemotherapy may be effective in alleviating the pain, but eventually the disease becomes refractory to these agents also (4). In limited metastatic disease, a short course of external-beam radiotherapy at a high dose per fraction effectively controls pain and has low toxicity, but toxicity rapidly increases as the field of irradiation increases (7,8).…”
mentioning
confidence: 99%
“…The most typical locations are vertebrae, ribs, pelvic bones, and skull (1)(2)(3). The therapeutic options are rarely (if ever) curative, and at some point most patients with osseous metastasis develop progressive disease, leading to a series of disease-related events that have the most significant impact on quality of life (4).…”
mentioning
confidence: 99%
“…A phase III randomized trial performed enrolling 152 patients, to assess t he effectiveness of Sm-153 for palliation of bone pain in patients with prostate cancer, showed st atistically significant improvement in analgesic consumption and pain. 14 In India, Tripathi et al 9 conducted a study, in 2006 to determine the efficacy and toxicity of single dose Sm-153 EDTMP as a palliative treatment for painful skeletal metastases and reported effective palliation in 73% patients. Most of the patients tolerated this treatment without any untoward event and major toxicity was temporary myelosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Their performance status was evaluated using the Karnofsky Performance Score (KPS). 8 For each patient, an analgesic score 9 was also computed as the product of analgesic type and administration frequency coded into integer form.…”
Section: Methodsmentioning
confidence: 99%